2022
DOI: 10.1039/d2sc01064j
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–chalcogen bond formation initiated by [Al(NONDipp)(E)]anions containing Al–E{16} (E{16} = S, Se) multiple bonds

Abstract: Multiply bonded main group metal compounds are of interest as a new class of reactive species able to activate and functionalize a wide range of substrates. The aluminium sulfido compound...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 85 publications
(134 reference statements)
2
18
0
Order By: Relevance
“…This is further supported by low WBI (Al–O) values ( 4-Zn = 0.372; 4-Mg = 0.426) when compared with the [Al(NON Dipp )(O)] − anion (WBI (Al–O) = 1.11). 23 Moreover, we note that the values of ρ ( r ) are similar to that of the monomeric [Al(NON Dipp )(O)] − anion ( ρ ( r ) = 0.115 e Å −3 ; ∇ 2 ρ ( r ) = 0.990 e Å −5 ), 23 indicating that the terminal M (BDI Mes ) group only minimally perturbs the charge density and electronic composition of the Al–O bond. A more pronounced difference is observed for the O– M BCPs in each compound.…”
mentioning
confidence: 82%
“…This is further supported by low WBI (Al–O) values ( 4-Zn = 0.372; 4-Mg = 0.426) when compared with the [Al(NON Dipp )(O)] − anion (WBI (Al–O) = 1.11). 23 Moreover, we note that the values of ρ ( r ) are similar to that of the monomeric [Al(NON Dipp )(O)] − anion ( ρ ( r ) = 0.115 e Å −3 ; ∇ 2 ρ ( r ) = 0.990 e Å −5 ), 23 indicating that the terminal M (BDI Mes ) group only minimally perturbs the charge density and electronic composition of the Al–O bond. A more pronounced difference is observed for the O– M BCPs in each compound.…”
mentioning
confidence: 82%
“…However, DFT studies revealed that as the chalcogenides get heavier the degree of multiple bonding tends to increase. 83 The exposure of the sulfide and selenide to an atmosphere of 13 CO2 resulted in the formation of the corresponding heavy carbonate complexes B-1.86-S and B-1.86-Se, similar to those observed by the related alumoxane complexes (Scheme 1.17). 83 However, the terminal telluride was identified to proceed through a heavy carbonate intermediate ("B-1.86-Te"), before undergoing another insertion of 13 CO2 to afford B-1.87-Te.…”
Section: Scheme 113 Fragmentation Of White Phosphoroussupporting
confidence: 57%
“…83 The exposure of the sulfide and selenide to an atmosphere of 13 CO2 resulted in the formation of the corresponding heavy carbonate complexes B-1.86-S and B-1.86-Se, similar to those observed by the related alumoxane complexes (Scheme 1.17). 83 However, the terminal telluride was identified to proceed through a heavy carbonate intermediate ("B-1.86-Te"), before undergoing another insertion of 13 CO2 to afford B-1.87-Te. 84 The addition of CS2 to B-1.81 was shown to form B-1.88, which forms via a [2+2]-cycloaddition across the "Al=S" bond.…”
Section: Scheme 113 Fragmentation Of White Phosphoroussupporting
confidence: 57%
See 2 more Smart Citations